2005
DOI: 10.1162/0034653053327559
|View full text |Cite
|
Sign up to set email alerts
|

Returns to Human Capital Under The Communist Wage Grid and During the Transition to a Market Economy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
138
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(154 citation statements)
references
References 17 publications
12
138
2
2
Order By: Relevance
“…As in other country-specific studies (e.g. Bird et al, 1994;Orazem and Vodipevic, 1994;Chase, 1998;Munich et al, 1999) and as found by Newell and Reilly (1999) in their study of nine transition countries, during transition, returns to education increase. However, in Bulgaria typically these returns to education are lower than elsewhere --compared with those found by Flanagan (1994) for the Czech Republic and with returns exceeding 7% in Germany and Poland (Rutkowski, 1994).…”
Section: Discussionsupporting
confidence: 75%
“…As in other country-specific studies (e.g. Bird et al, 1994;Orazem and Vodipevic, 1994;Chase, 1998;Munich et al, 1999) and as found by Newell and Reilly (1999) in their study of nine transition countries, during transition, returns to education increase. However, in Bulgaria typically these returns to education are lower than elsewhere --compared with those found by Flanagan (1994) for the Czech Republic and with returns exceeding 7% in Germany and Poland (Rutkowski, 1994).…”
Section: Discussionsupporting
confidence: 75%
“…In the first systematic study of income and wage inequality in former communist countries, Atkinson and Mickelwright (1992) argued that, beyond the communist ideology, inequality was not low, that the returns to education were at least as high and the returns to work experience were as concave as in the West. Similar conclusions are reached in Katz (1999) and Munich, Svejnar and Terrell (2002). Conversely, Benitez-Silva and Cheidvasser (2000) claim 2 This statement is based on the idea that market criteria existing in Western countries are the benchmark to evaluate efficiency also in former Socialist economies.…”
Section: Wages Under the Central-planning Systemmentioning
confidence: 76%
“…With the exception of the work of Rutkowski (1999) and Jones and Simon (2004), this study is also the only other attempt to estimate the trends in returns to schooling in Bulgaria. Finally, we consider our measure of the number of years of schooling to be more accurate than the one adopted in many other studies (e.g., Brainerd, 1998;Flanagan, 1998;Vernon, 2002), since we use the number reported by the respondents themselves, rather than an imputed value derived from the reported school attainment (see Munich, Svejnar, & Terrell, 1999).…”
Section: Article In Pressmentioning
confidence: 99%